FRI0394 Assessment of Cardiovascular Risk Factors in Patients with Spondyloarthritis and Their Association with Disease Features and Its Activity. A Comparison between Two Population Groups from Asas-Comospa. (15th July 2016) - Lόpez-Medina, C.; Font-Ugalde, P.; Calvo-Gutiérrez, J.; Castro-Villegas, M.C.; Ortega-Castro, R.; Escudero-Contreras, A.; Collantes-Estévez, E.
Abstract : Background: Data from epidemiologic studies suggest that patients with Spondyloarthritis (SpA) have an increased risk of developing cardiovascular disease 1 (CVD). In healthy people this risk is different depending on the country, ambient factors and lifestyle. However, in SpA patients these differences have not been studied yet, so it is unknown whether they are attributable to the socio-demographic factors or to the disease itself and its activity. Objectives: To assess the prevalence of cardiovascular risk factors in SpA patients by making a comparison between two population groups which have socio-demographic differences, and to recognize the items which define the variability of the Framingham risk score. Methods: An observational, cross-sectional and multicenter study which included 1982 patients with SpA selected from the ASAS-COMOSPA register and belonging to two groups of countries: Northern Europe (UK, Germany, Belgium and Netherland) and Mediterranean Basin countries (Spain, France, Italy, Morocco, Turkey and Egypt). Univariate logistic regressions, stratified by sex and disease duration (with a cut-off of 10 years) were performed to contrast the two groups of countries and the cardiovascular risk factors (smoking, BMI, dyslipidemia, diabetes, renal deficiency, family history, ischemic heart disease and stroke). A multiple linear regression was performed in order to determine the variability in Framingham risk score attributable to different items (socio-demographics, disease related factors and disease activity). Results: There were 1336 (67.40%) patients from Mediterranean basin countries and 646 (32.60) from Northern Europe; 797 (40.21%) were women and 1185 (59.78%) were men. Men and women from Northern Europe have a higher frequency in smoking (OR 1.85 and OR 1.37 respectively). However, for both sex, HTA (OR 0.48 and OR 0.45) and ischemic heart disease (OR 0.25 and OR 0.29) is less frequent than in those from Mediterranean countries. It is less frequent obesity (OR 0.70 and OR 0.50), HTA (OR 0.49 and OR 0.59) and ischemic heart disease (OR 0.21 and OR 0.47) in patients from Northern Europe countries, both in a disease duration of <10 and ≥10 years respectively, than in patients from Southern countries. In patients with a disease duration of <10 years, it is also less usual dyslipidemia (OR 0.66) and renal deficiency (OR 0.24). In the overall population, 70.5% of Framingham risk score was explained by sex, age, disease duration, belonging to Northern countries, current smoking, number of tender joints, physician's global assessment (all of them p<0.001) and erythrocyte sedimentation rate (being the latter one a confounding factor, p=0.091). Conclusions: Northern Europe patients with SpA have a lower cardiovascular risk than those from Mediterranean basin countries, both women and men. However these differences can't be only attributable to socio-demographic characteristics, because disease related factors and disease activity are contributory causes in the appearance of cardiovascular risk. References: Bremander A, et al. Population-based estimates of common comorbidities and cardiovascular disease in ankylosing spondylitis. Arthritis Care Res (Hoboken) 2011;63:550–6. Disclosure of Interest: None declared